Forecasting and verification of winds in an East African complex terrain using coupled mesoscale - And micro-scale models. Issue 176 (May 2018) - Mughal, Muhammad Omer; Lynch, Mervyn; Yu, Frank; Sutton, John
Abstract: A novel technique for micro-siting and forecasting appropriate to wind farms has been developed. The modelling approach was tested with a selection of different physical options and initialization fields at a complex geographical location characterised by a contrasting diurnal meteorological cycles. An improvement of 10% in wind speed forecasting was achieved by coupling a mesoscale model to a microscale model; the latter was based on Large Eddy Simulation (LES). The platforms for meso and microscale modelling were the Weather Research and Forecasting (WRF) and OpenFOAM models respectively. Highlights: Development of a novel technique for micro-siting and forecasting appropriate to wind farms. The modelling approach involves coupling of meso and microscale models. 10% improvement in wind forecasting achieved through coupling. The study demonstrated the capacity to contribute to wind farm design as well as improved wind energy forecasting.